Demografia do Afeganistão: presente e futuro de treze províncias selecionadas - Vanessa Cardoso Ferreira (2021)
Afghanistan is a country that has experienced years of intense crises, which created a context of high social vulnerability and has impacted its population structure. However, the magnitude of this process has been ineffectively translated into numbers, due to a deficiency in the historical production of national statistics for the country – in Western terms. Despite the development and relative recovery of the country since 2002, with the international agencies of cooperation at the country, little is known about its population dynamics, partly due to the scarcity of data, given that the last census was carried out in 1979. This thesis contributes to reduce these gaps by providing estimates of present and providing future estimates considering different scenarios of fertility, mortality and migration – the three variables that define the demographic structure of a population. The study was structured for thirteen selected provinces of Afghanistan from census-type data collected between 2011-2017 in the Socioeconomic and Demographic Survey (SDES) of responsibility of The Central Statistics Office of Afghanistan and the United Nations Population Fund. The provinces as a whole represent more than 50% of the Afghan population. Before the analysis itself, the thesis assesses the degree of consistency, reliability and complexity of the data, and provide adjustments in some cases in order to obtain the best possible estimate. For this purpose, demographic indicators are presented using direct and indirect methods of analysis, allowing the best possible approximation to the real demographic profile that the provinces would present. This is achieved through a careful assessment of the population structure, fertility, mortality and migration of the provinces selected in the SDES. Finally, a base population is defined for the construction of future estimates, for a thirty years period. This work benefits from the studies carried out within the scope of the SDES project and proposes to be a continuation of the diagnosis carried out by it. As a first contribution and an advance in relation to what had already been done, the thesis presents an analysis of the information quality, by sex and age, of these data, in order to identify problems related to coverage errors and information declaration. Similar to the Demographic Conciliation processes, an attempt was made to determine how reliable the data sources used are. A second contribution is the incorporation of new adjustments and parameters to the direct and indirect demographic methods that had already been presented before this thesis, such as, for example, in the part of adult mortality. What is offered here is, therefore, a new possibility of outcome, following alternative assumptions. To better contextualize the Afghanistan, a historical synthesis of the main events in the country since 1929 was carried out, and how historical factors impacted the production of national statistics over the years. In this context, the main researches that were developed and are accessible for public consultation are presented. From these researches, the socioeconomic aspects of the focus provinces were contextualized, noting situations of extreme social vulnerability associated with demographic indicators. Also denouncing this vulnerability, when pointing the high mortality in childhood (above 100.0 per thousand) for the provinces of Daykundi, Bamyian, Badghis, Baglhan, Herat, Nimroz, Samangan e Takhar, between 2011 and 2017, or the high risk of teenage women having a child when they marry. The prospective estimates cover a period of 30 years and consider the characteristics of each province, its population structures, its mortality and fertility patterns, as well as a zero-migration balance. Although the thesis analyzes data referring to migration by measuring the intensity of migratory flows, especially those involving the province where the capital, Kabul, is located, the thesis does not include the migration component in the population projections, due to the lack of comparison of this item with the over the years.The projection, elaborated via the Demographic Components Method (in which fertility, mortality and migration are considered separately), allows us to define the numerous prospective scenarios that the population would experience in the next 30 years. However, it is only through three scenarios defined as plausible that the thesis shows the probable future population contingent of the Afghan provinces analyzed here. The considered scenarios are: a) Constant: predicts that fertility and mortality levels and patterns will remain constant throughout the projection period. Besides being an plausible scenario, the results allow us to measure the effect on the population of changes in other scenarios to be developed; b) Moderate: predicts that the fertility level will reduce moderately and a decline in mortality levels if the development of Afghan society remains with the demonstrated rhythm until the end of 2020; c) Accelerated: predicts that the level of fertility will drastically reduce whether certain strategies are implemented and a decline in mortality levels, similar to the specified at (b) scenario. The hypotheses, on which these scenarios are based, incorporate the most recent evidence recorded until the end of 2020. Therefore, they do not contemplate the events of 2021, which will probably print different directions to the course of Afghan history. In general terms, and depending on the scenarios to materialize in the future, the Afghan provinces studied here would maintain an average annual growth rate ranging between 3.0% and 1.5% in Kabul (the most developed province) and between 3.7% and 1.95% in Ghor (one of the least developed provinces). It is important to mention that, due to the population structure that each province has, the population growth will be, for a few five years, very expressive and maintaining the character of being provinces with a very young population profile. This is valid for the whole country, since, most likely, provinces not covered in this study are demographically very similar. Considering the social development achieved until the end of 2010 decade and assuming its continuation, the mortality implicit in these scenarios predicts an increase in life expectancy at birth, which would reach a maximum value of 77.1 years for men and 79, 5 years for women, on average for Afghanistan. In this same line of reasoning, it would be expected that the average number of children had by women could decrease between the initial period of the research and 2030. A rate of fertility change is assumed for each province, taking as a mirror what happened in Iran and Pakistan, countries with sociocultural patterns very similar to those of Afghanistan. Thus, for Kabul, starting from a total fertility rate (TFT) of 5.02 children per woman, it would fall to 2.40 or 1.66, according to the Moderate and Accelerated Scenarios, respectively. In Ghor, likewise, the original TFT of 7.29 would drop to 3.27 or 2.24. The results obtained show the population trends of these provinces, if the scenarios defined here are verified. They are an important resource to be incorporated in the future planning and initiatives that Afghanistan could follow to seek social development of its population. Additionally, we believe that it can serve as a demographic reference to provinces that currently do not have data, for example, the ones which were not contemplated at the SDES 2011-2017.